Worldly development in the light of Seerah and the practice of contemporary - Dr. Abdur Rahman Khalid Madni; Muhammad Shahzad Imran (jihat-ul-islam, 2022)
Allah sent the greatest of human beings Muhammad (peace and blessings of Allah be upon Him), the last Messenger of Allah, as a mercy to all the universe, as his last and greatest Prophet, made His religion, His favorite religion, and given the status to His nation the best nation. This Ummah, under the guidance and training of their Holy Prophet (peace and blessings of Allah be upon Him), illuminated the dark night of humanity and made the forgotten man self-aware and God-knowing. Then this Ummah, following the teachings of their Prophet (peace and blessings of Allah be upon him), performed the duties of Imamate of the people of the world and enlightened the whole world with the light of knowledge and mysticism, progress, prosperity, peace and reconciliation۔ Then gradually this Ummah began to forget the teachings of their Prophet (peace and blessings of Allah be upon Him) and established the love of the world in their hearts. As a result, knowledge and mysticism turned away from them and they lag far behind the rest of the world in development and prosperity. Muslims have a lot of resources today but they are still humiliated. This research paper will explore, how Muslims will be prosperous and successful again in the world. What are the reasons that Muslims are suffering so much all around the Word and what is the solution of the problems of contemporary Muslims?